KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR BERKALA ANGKUTAN KOTA DI KOTA BOGOR - rahmawati, evi; Purnamasari, irma; Goris Seran, Gotfridus (Administratie: Jurnal Administrasi Publik, 2019)
Testing of Motor vehicle transportation is a form of public service that aims to inspect roadworthy vehicles. This public service is vital because it determines road safety. This study aims to find the quality of periodic testing services in city transportation. This research uses a descriptive method with a quantitative approach. The population in this study was 377 vehicle owners who received testing services. Determination of the sample using the formula Yamane. The result was 79 respondents. Also, the sample of this study was 18 testing staff. Data collection techniques used literature study, observation, interviews, and questionnaires. Data analysis uses Weight Mean Score (WMS) calculations. This study produces an average data score of 3.93 (out of the highest score of 5) for assessing the quality of public services testing motor vehicles, which it showed proper criteria. It means that the quality of service already done well. However, there are still complaints from the public regarding parking areas and waiting rooms, which the community assesses as still lacking, so the facilities need to be improved.